INVESTIGATING THE STAGES AND THE POTENTIALS OF IMPLEMENTING CLINICAL SUPERVISION - Nurhidayat, M. Fikri; Masrukan,; Rusilowati, Ani (Idaarah: Jurnal Manajemen Pendidikan, 2022)
Abstract: Investigating the Stages and the Potentials of Implementing Clinical Supervision Teachers are an important pillar of education. Guidance for teachers in the form of supervision should be carried out properly. One type of supervision that can be done is clinical supervision. The purpose of this study was to describe the stages of clinical supervision, and to analyze the potential for implementing clinical supervision. This research is literature review research carried out in four stages, namely searching the reference, identification, discussion, and drawing conclusions. The literatures reviewed were 20 articles and 7 books both nationally and internationally. The results showed 1) The stages of clinical supervision include planning, implementation, and evaluation; 2) The potential for implementing clinical supervision is excellent because it can improve pedagogic competence, and instructional competence finally able to produce professional teachers. It can be concluded that clinical supervision is an important part of teacher professional development.